أساليب السرد القصصي عبر التسويق الرقمي لدى المؤسسات الخدماتية الجزائرية - قادري, ريم نهاد (كلية العلوم الاجتماعية, 2025)
تهدف هذه الدراسة إلى تحليل أساليب السرد القصصي في التسويق الرقمي المعتمدة لدى مؤسستي أوريدو وجيزي عبر تطبيق إنستغرام، مع التركيز على كيفية توظيف القصص الرقمية للترويج للخدمات وجذب الجمهور. حيث تم تحليل عينة من الإعلانات المنشورة على الصفحات الرسمية للمؤسستين. استندنا في بحثنا على منهجين تمثلا في المنهج الوصفي، المسحي، واستخدمنا استمارة تحليل المضمون كأداة لجمع البيانات، ومجتمع البحث الذي تمثل في جميع الإعلانات الرقمية لمؤسستي أوريدو وجيزي المنشورة على تطبيق الإنستغرام والتي تضمنت أسلوب السرد القصصي، وعينة قصدية مكونة من ستة إعلانات (3 من كل مؤسسة)، نظراً لتمثيلها الواضح لتقنيات السرد القصصي. وقد أظهرت النتائج أنّ: • نجحت المؤسستين في توظيف عناصر بصرية ولغوية متناسبة مع خصائص الجمهور المحلي وطبيعة المنصة. • أكدت النتائج أهمية التكيف مع التطورات الرقمية لتعزيز فعالية الحملات التسويقية، مع التركيز على التنوع في القصص والعناصر الفنية لتحقيق الأهداف التسويقية. This study aims to analyze the storytelling methods in digital marketing adopted by the Algerian service institutions Ooredoo and Djezzy through the Instagram application, with a focus on how digital stories are utilized to promote services and attract audiences. A sample of advertisements published on the official Instagram pages of both institutions was analyzed. The research relied on three main methodologies: the descriptive, survey, and comparative approaches. A content analysis form was used as the primary data collection tool. The research population consisted of all digital advertisements published by Ooredoo and Djezzy on Instagram that employed storytelling techniques. A purposive sample of six advertisements (three from each institution) was selected due to their clear representation of storytelling strategies. The results revealed that: • Both institutions successfully employed visual and linguistic elements aligned with the characteristics of the local audience and the nature of the platform. • The findings confirmed the importance of adapting to digital advancements to enhance the effectiveness of marketing campaigns, with an emphasis on story diversity and artistic elements to achieve marketing objectives.
دراسة تحليلة لعينة من الإعلانات المؤسستي أوريدو وجيزي
Keywords: التسويق الرقمي، السرد القصصي، المؤسسات الخدماتية.